On Digital Citizenship Research in Journals in the TR Index Database: A Systematic Compilation Study - Hakan Öngören (İletişim Kuram ve Araştırma Dergisi)
The concept of digital citizenship is met with great interest in the academic community and is the subject of the research. Since the number of studies conducted has increased with the interest in question, it has become important to know the studies and their general trends. In the study designed with the systematic compilation model, the data were obtained from published research on digital citizenship in journals scanned in the TR Index index. In this context, 38 scientific researchers were examined on the basis of systematic compilation patterns from qualitative analysis methods. Accordingly, the distribution of the number of studies examined by year, the period of acceptance for publication, the journal name of the studies, the methods used in the research, data collection tools, validity and reliability analyses, and data analysis methods related to the data have been tabulated and graphed with frequency and percentage calculations. According to the results obtained from the research, it was concluded that the journals with the highest number of publications are in the field of educational sciences; the period of acceptance for publication is between 0 and 3 months; the qualitative research method is mostly used; the sample group is between 101-300 people; and the sample number is between 301-1000 people.